2017
DOI: 10.1016/j.nbd.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

APC conditional knock-out mouse is a model of infantile spasms with elevated neuronal β-catenin levels, neonatal spasms, and chronic seizures

Abstract: Infantile spasms (IS) are a catastrophic childhood epilepsy syndrome characterized by flexion-extension spasms during infancy that progress to chronic seizures and cognitive deficits in later life. The molecular causes of IS are poorly defined. Genetic screens of individuals with IS have identified multiple risk genes, several of which are predicted to alter β-catenin pathways. However, evidence linking malfunction of β-catenin pathways and IS is lacking. Here, we show that conditional deletion in mice of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 59 publications
3
41
0
Order By: Relevance
“…Adenomatous polyposis coli (APC) is a negative regulator of β-catenin/Wnt signaling. Interestingly, multiple human mutations that cause IS involve proteins that modulate, or are modulated by, β-catenin signaling (see Pirone et al for a summary [32]). In line with a hyper-excitation phenotype, genetically removing APC from excitatory forebrain neurons using CamKII-cre results in increased dendritic spines on hippocampal CA1 neurons, increased excitatory neurotransmission, and autistic-like behavior in adults (31).…”
Section: Apc Cko Mouse Modelmentioning
confidence: 99%
“…Adenomatous polyposis coli (APC) is a negative regulator of β-catenin/Wnt signaling. Interestingly, multiple human mutations that cause IS involve proteins that modulate, or are modulated by, β-catenin signaling (see Pirone et al for a summary [32]). In line with a hyper-excitation phenotype, genetically removing APC from excitatory forebrain neurons using CamKII-cre results in increased dendritic spines on hippocampal CA1 neurons, increased excitatory neurotransmission, and autistic-like behavior in adults (31).…”
Section: Apc Cko Mouse Modelmentioning
confidence: 99%
“…Several animal models of IS or WS or epileptic spasms have been developed [reviewed in (Galanopoulou & Moshe 2015); also see (Dube, Molet, Singh-Taylor, Ivy, Maras & Baram 2015, Pirone, Alexander, Lau, Hampton, Zayachkivsky, Yee et al 2016)]. The investigation of inflammatory pathways in IS has been done so far in the multiple-hit rat model, which will be described below.…”
Section: Does Activation Of the Inflammatory Pathways In The Brainmentioning
confidence: 99%
“…We found that Tsc1 GFAP CKO mice did have a reduced threshold and increased frequency of NMDA‐induced spasms, suggesting an increased propensity for spasms, although no spontaneous spasms were observed on subsequent days beyond the acute period after NMDA injection. Other “two‐hit” approaches, such as combining an inflammatory insult or other genetic mutations with Tsc1 GFAP CKO mice, could potentially be used to generate a chronic model of infantile spasms 33,39,40 …”
Section: Discussionmentioning
confidence: 99%